ANTS AS BIO-CONTROL AGENTS OF UZI FLY, BLEPHARIPA ZEBINA WALKER (DIPTERA : TACHINIDAE) AN ENDOPARASITE OF OAK TASAR SILKWORM IN MANIPUR - VENKATACHALAPATHY, M.; PRASAD, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1999)
Ants have been observed to be important predators of uzi fly maggots and pupae and thus reducing the uzi fly population in the oak tasar farms and grainages Four species of such ants were recorded and have been identified for the first time from North-East India.